2009
DOI: 10.1111/j.1745-6606.2009.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Literacy of Older Adults

Abstract: We developed an instrument to measure dimensions of health insurance literacy reflecting familiarity with health insurance terminology and proficiency with the Medicare program. The instrument's items were based on a conceptual framework integrating the financial and health insurance literacy fields and were fielded in a national survey of older adults. We found that overall levels of health insurance literacy were low to moderate. The oldest adults, those with lower education and income, and those with poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 20 publications
6
90
1
3
Order By: Relevance
“…– in short, the hassles that anyone who uses the U.S. health care system is familiar with, but that may loom larger for individuals with low health literacy. The relatively new concept of “health insurance literacy” (Kim, Braun, & Williams, 2013; McCormack, Bann, Uhrig, Berkman, & Rudd, 2009; Paez, Mallery, Noel, Pugliese, McSorley, Lucado, & Ganachari, 2014) encompasses both of these mechanisms. Our results suggest that lower rates of health insurance coverage are not the only reason individuals with low health literacy experience worse access, but this does not mean that health insurance is irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…– in short, the hassles that anyone who uses the U.S. health care system is familiar with, but that may loom larger for individuals with low health literacy. The relatively new concept of “health insurance literacy” (Kim, Braun, & Williams, 2013; McCormack, Bann, Uhrig, Berkman, & Rudd, 2009; Paez, Mallery, Noel, Pugliese, McSorley, Lucado, & Ganachari, 2014) encompasses both of these mechanisms. Our results suggest that lower rates of health insurance coverage are not the only reason individuals with low health literacy experience worse access, but this does not mean that health insurance is irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…One review of 85 studies found that the prevalence of low and marginal health literacy among older American adults was estimated around 20% (McDougall, Mackert, & Becker, 2012). The oldest adults, those with lower education and income, and those with poorer health had lower levels of health insurance literacy (McCormack, Bann, Uhrig, Berkman, & Rudd, 2009). Health literacy is especially critical for managing medication, since adults over age 65 years use over 30% of all prescription medications (McDougall et al, 2012, p. 71).…”
Section: The Problem and Prevalence Of Low Health Literacy Among Oldementioning
confidence: 98%
“…To date, most research has focused on the association between HIL and demographics. In McCormack et al's () research on HIL in older Americans, the authors found that HIL was low to moderate in older Americans, but also found HIL to be weakest in older adults, those with lower education, lower income, and poorer health. Research by Bartholomae et al () also found HIL to be related to socio‐demographics, where consumers who earned higher incomes, were older, female, and higher educated demonstrated greater initial HIL scores compared to their counterparts (i.e., middle‐income consumers, younger, male, and lower educated).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…To address this gap, we draw from research that examined the association of psychographics with financial literacy (e.g., O'Connor ; Perry and Morris ), the association of financial literacy with HIL (McCormack et al ), as well as research in psychology (e.g., Hoorens and Buunk ; Judge and Bono ) to identify consumer characteristics that influence a consumer's HIL. We first consider how an individual's expectations of control (i.e., LOC) are related to their HIL.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%